Universiti Malaysia Terengganu prihatin: mengharungi cabaran pandemik Covid-19 - Zakariya, Hafiz (Universiti Malaysia Terengganu Press, 2021)
This study documents the efforts of UMT in managing the COVID-19 during the initial phase of the Movement Control Order from 18 March 2020 to 31 May 2020. It highlights the major challenges, roles and services provided by the Office of Student Affairs Division to its students. Besides it discusses some silver lining behind the pandemic.